2010
DOI: 10.1111/j.1447-0349.2010.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of succession planning for mental health nurse practitioners

Abstract: This paper reviews current literature on succession planning for mental health nurse practitioners (NPs) and discusses a model of succession planning that is underpinned by principals of leadership development, workforce participation and client engagement. The paper identifies succession planning as a means of managing a present and future workforce, while simultaneously addressing individual and organizational learning and practice development needs. A discussion of the processes attendant upon sustainable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…, Hampel et al . ) in order to get both subordinate and managerial nurses prepared for advancement into even more challenging roles in the hospitals. Consistent with previous findings that have shown internals to be more adaptive in dealing with task‐related problems (Spector , Rodriguez et al .…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
“…, Hampel et al . ) in order to get both subordinate and managerial nurses prepared for advancement into even more challenging roles in the hospitals. Consistent with previous findings that have shown internals to be more adaptive in dealing with task‐related problems (Spector , Rodriguez et al .…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
“…Another finding is that satisfaction was higher among nurses with post basic-training as opposed to no training. The ability to retain nurses in the profession is influenced mainly by the perception of career options and satisfaction (Hampel, Procter, & Deuter, 2010). Therefore, a policy based on examining the nurses' positions regarding their activity, their satisfaction and areas perceived to require expanded authorities and/or additional training will be an important step in exhausting the existing potential and expanding the practice areas in psychiatry.…”
Section: Workforce Considerationsmentioning
confidence: 99%
“…11 It was also identified that succession planning requires formal organizational support and resource commitment for direct patient care roles. 10 Succession planning is vital to sustaining the mission of professional associations. The Texas Nurses Association (TNA) initiated an emerging nurse leaders program as an approach to engaging new nurses in the leadership of the association.…”
Section: Literature Reviewmentioning
confidence: 99%